Itinerancy. Dispersal, migration, diaspora - Ester Desfilis; Domingo Pujante González (Mètode Science Studies Journal: Annual Review)
Most animals move from one place to another at some time in their lives. These movements may be undertaken by individuals or by groups, and species may colonize new habitats or join new social groups or populations away from their birthplace. Indeed, humans are a highly mobile species, dispersed far and wide. The first migration led some groups away from the African continent to colonize the rest of the planet and, ever since, geographical displacement of individuals or groups has remained constant throughout history (despite the restrictions currently imposed by border-control policies). Although there are many causes of migration, the ultimate goal is to improve chances of survival and/or reproduction.